The employee experience advantage : how to win the war for talent by giving employees the workspaces they want, the tools they need, and a culture they can celebrate - Morgan, Jacob, 1983- (John Wiley, 2017)
Featuring exclusive case studies, unique frameworks, and never before seen research, this book explains how to rethink your strategy and implement a real-world framework that focuses on how to create an organization where people want to show up to work. --